Investigating the Psychological Impacts of the COVID-19 Pandemic on University Students of Health Sciences Courses and Associated Factors - Merve Bat Tonkuş; Ece Alagöz; Behice Belkıs Çalışkan (Association of Nurse Managers, 2023)
Aim: The aim of this study was to determine the psychological impacts of the COVID-19 pandemic and associated factors on students of health sciences courses. Method: The population of the study consisted of students from all universities providing associate and undergraduate education in the field of health in Turkey. The sample of the research consists of 520 students. The research data were collected online using a descriptive characteristics form, the Impact of Events Scale (IES), and the Depression Anxiety Stress Scale (DASS). Mann-Whitney U, Kruskal-Wallis tests, and Spearman Correlation analysis were used to evaluate the data. Findings: According to the findings, the mean scores of women whose families had indifferent attitudes and those with psychiatric disorders were significantly higher (p<0.05). Emotionally stable students had significantly lower IES scores than other students. (p<0.01). It was determined that the total and sub-dimension scores of DASS were significantly lower in those whose families exhibited a tolerant and democratic attitude than those whose families had an authoritarian and indifferent attitude (p<0.05). Female participants had significantly higher mean scores in the DASS and Depression Anxiety sub-dimensions (p<0.05). Those with chronic diseases had significantly higher mean scores on the DASS. Those who defined their mood as stable during the pandemic process had significantly lower mean scores in the DASS and its sub-dimensions. A significant positive correlation was found between IES and DASS and its sub-dimensions (p<0.001). Conclusion: When these results were evaluated, it was determined that female students were negatively affected by the pandemic and experienced depression and anxiety, while those with a stable mood were less affected by the events and experienced less depression, anxiety, and stress. It was also concluded that those whose families were tolerant and democratic were less affected by the pandemic and experienced lower levels of depression, anxiety, and stress. Psychological impacts are related to the level of being affected by events.